2003
DOI: 10.1002/bjs.4356
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predicting the development of complications after foreign body ingestion

Abstract: In patients with a foreign body seen on plain cervical radiography, presentation delayed for more than 2 days after ingestion, and foreign body impacted at the level of the cricopharyngeus or oesophagus there is a high degree of correlation with the occurrence of complications. Awareness should be raised when these risk factors are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
157
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(187 citation statements)
references
References 10 publications
5
157
0
12
Order By: Relevance
“…In adults it can be accidental ingestion of an ill-fitting partial denture, under alcohol intoxication or in a patient with psychiatric illness or mental retardation. 12,13 The common age group in children where FB ingestion is common is between 6 months and 6 years. Patients can present with foreign body sensation, drooling, respiratory distress due to tracheal compression, vomiting and dysphagia, depending on the location and nature of foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…In adults it can be accidental ingestion of an ill-fitting partial denture, under alcohol intoxication or in a patient with psychiatric illness or mental retardation. 12,13 The common age group in children where FB ingestion is common is between 6 months and 6 years. Patients can present with foreign body sensation, drooling, respiratory distress due to tracheal compression, vomiting and dysphagia, depending on the location and nature of foreign body.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A study of 1,338 patients by Lai et.al revealed that the commonest location for a foreign body was the valleculae (31.4%). 4 On most occasions, the ingested fishbone passes uneventfully through the gastrointestinal tract within one week. 5 However, ingestion of foreign body may pose a potentially lethal risk, which mandates surgical exploration.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Lai et al studied 29 cases of foreign body ingestion followed by complications to assess the risk factors which predict the occurrence of the latter. 7 They included age, delayed presentation, comorbidities, cricopharyngeal impaction and radiographic identification. A case series demonstrated that oesophageal perforation may occur within 24 hours of ingestion whereas neck abscesses following ingestion may present after 4 or more days.…”
Section: Discussionmentioning
confidence: 99%